Assessing the Impact of Parenting Styles on Teen Independence in Rural Contexts - Yani Suryani; Sri Nurhayati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research examined the interplay between parenting styles, socio-economic and cultural conditions, and adolescent independence in rural settings. Utilizing qualitative approach with case study method, the study gathered insights from parents and adolescents in rural communities to understand how different parenting approaches implemented and how they are influenced by the unique characteristics of rural life. Findings reveal a prevalent use of democratic parenting styles in these settings, characterized by significant child involvement in decision-making and open communication about family expectations and responsibilities. This approach not only fosters independence but also instills crucial social values and collaborative skills in the youth. The study highlights the integral role of community in the educational framework, showing how communal support and shared cultural values shape and reinforce educational practices and adolescent development. Economic factors and government interventions are also noted as significant influences on parenting styles and educational opportunities, with parents adapting their methods according to changing economic landscapes and available resources. The research concluded that effective educational strategies in rural areas require a holistic approach that integrates family, community, and broader socio-economic contexts, thereby supporting the comprehensive development of rural adolescents. This study contributes to the broader discourse on rural education, providing valuable insights for policymakers and educators in designing community-specific educational programs.